Prophetic Guiding Principles for Human Behaviour Related to Land (Lithosphere) as an Element of Our Environment - Sumaira Nawaz; Dr. Shah Moeen ud Din Hashmi (Al Basirah, 2021)
Human behaviour is the fundamental problem regarding the imbalance relation of environment and mankind. Most of the Muslims societies are not well aware about current environmental crises and its impact on nature. Islamic teachings especially prophetic tradition focused on the precautionary behaviours by Muslims for protecting the environment from all types of catastrophe. The study highlights some strategies for preserving natural resources especially land and protecting human being from environmental hazards on individual basis as daily routine life. That is quite protective or environment friendly according to modern environmental studies. The paper has descriptive and analytical approaches with pro environmental behaviours with empirical treatment of textual study of Ahadith, which transpire all prophetic guiding principles in conservation of environment from all dangers. The study concludes with the number of recommendations and strategies such as need of awareness and implementation about the prophetic approach regarding environmental behaviours; formation of scientific committee with expertise of textual studies of Hadith, Quran and Fiqh as well as environmental sciences; media campaign for raising awareness of environmental issues on local level for layman.